Using a non-parametric technique to evaluate the efficiency of a logistics company - Průša, Petr; Jovčic, Stefan; Samson, Josef; Kozubíková, Zuzana; Kozubík, Aleš (My University, 2020)
Data Envelopment Analysis (DEA) is a relatively new method, a nonparametric technique used nowadays to evaluate the efficiency of the Decision-Making Units. Using this method, the Decision-Making Units can be compared between each other and the most effective ones can be found. Using the DEA method, the performance of a logistic company with twelve warehouses as DMUs is evaluated in this paper. "DEA Excel Solver" user program was used to solve the problem.
Využití neparametrické techniky k hodnocení efektivnosti logistické společnosti
Keywords: warehouse; logistics; efficiency; Data Envelopment Analysis; decision-making units; sklad; logistika; účinnost; analýza datových obálek; rozhodovací jednotky